Cocaine-induced epigenetic DNA modification in mouse addiction-specific and non-specific tissues. (1st September 2018) - Anier, Kaili; Urb, Mari; Kipper, Karin; Herodes, Koit; Timmusk, Tõnis; Zharkovsky, Alexander; Kalda, Anti
Abstract: Cocaine-related DNA methylation studies have primarily focused on the specific brain regions associated with drug addiction (e.g., the nucleus accumbens, NAc). To date, no studies have focused on the complex role of both DNA methylation and demethylation in the mechanisms of psychostimulant-induced addiction in the brain and peripheral tissues. Therefore, in this study, we evaluated cocaine treatment and withdrawal (animals were withdrawn from seven days of repeated injections of cocaine that caused behavioral sensitization) effects on epigenetic DNA modifiers (i.e., DNA methyltransferases, [DNMTs] and ten-eleven translocation enzymes [TETs]) in an addiction-specific brain region (NAc), a structure outside the mesolimbic dopaminergic system (cerebellum, Cer), and in peripheral blood cells (PBCs). Using a mouse behavioral sensitization model, we demonstrated that acute cocaine (AC; 0.5 h) treatment significantly decreased Dnmt1, Dnmt3a, Tet1, and Tet2 mRNA levels in the NAc and PBC, whereas at 24 h after AC treatment, Dnmt mRNA expression and enzyme activity levels were significantly increased. Acute procaine treatment caused the opposite effect on the Dnmt3a mRNA level in PBCs; this outcome suggests that the inhibition of voltage-gated sodium channels may be the mechanism that alters Dnmt expression in PBCs. Cocaine withdrawal is associated with increased expression of Dnmt s in the NAc, Cer and PBCs and the decreased expression of Tet1 and Tet3 in the NAc. Additionally, cocaine withdrawal increased DNMT but decreased TET activity levels, and these changes were associated with enhanced global and selected candidate gene promoter-region DNA methylation and hydroxymethylation levels in the NAc and PBCs. Together, these data indicate that cocaine treatment and withdrawal affect the expression of epigenetic DNA modifiers in both addiction-specific brain structures and structures outside of the mesolimbic dopaminergic system and PBCs. Highlights: Complex role of DNA methylation and demethylation in the mechanisms of addiction. Cocaine alters epigenetic DNA modifiers in nucleus accumbens and cerebellum. Cocaine alters epigenetic DNA modifiers in peripheral blood cells. Cocaine withdrawal enhances the expression of epigenetic DNA modifiers. Cocaine withdrawal alters the global balance of DNA methylation and demethylation.